Comment on "Quantify the contribution of chain length heterogeneity on block copolymer self-assembly". (March 2021) - Lai, Chi To; Shi, An-Chang
Highlights: The experimentally observed domain spacing and order-disorder transition point are found to be in excellent agreement with theoretical predictions, implying that a combination of experimental techniques and theoretical modelling would offer exciting opportunities to engineering desirable block copolymer morphologies using block copolymers with designed chain length heterogeneities. Graphical abstract: Abstract: The effects of molecular weight distribution on the self-assembly of lamella-forming AB-diblock copolymers with polydisperse A-blocks are examined using the self-consistent field theory applied to the freely-jointed chain (FJC) model of polymers. The experimentally observed domain spacing and order-disorder transition point are well described by the theory. The excellent agreement between experiments and theory indicates that the FJC model is capable of describing the phase behaviour of low-molecular block copolymers. A combination of experimental techniques and theoretical modelling offers exciting opportunities to engineering desirable block copolymer morphologies using block copolymers with designed chain length heterogeneities.